PENGARUH SOCIAL IDENTITY, EWOM, PERCEIVED RISK, DAN TRUST TERHADAP PURCHASE INTENTION DAN DAMPAKNYA TERHADAP PURCHASE DECISION PADA E-COMMERCE - Tessa Handra; Felix Sutisna (Jurnal Bina Manajemen, 2021)
This study was designed to test empirical truths between two or more research variables that have been formulated in the hypothesis. The research variables tused twere social identity, EWOM, perceived risk, trust, purchase intention, tand tpurchase decision. Exogenous variables in this study are social identity, EWOM, and perceived risk. Endogenous variables in this study are trust, purchase intention, and purchase decision. Methods of collecting data using questionnaires and data analysis methods using partial least square. The results of the study concluded that hypothesis 4 tand 5 was tnot significant. There was no effect of perceived risk on trust and there was no effect of perceived risk on purchase intention.